Παγκοσμιοποίηση και εκπαίδευση: Ο ρόλος της θρησκείας στα Αναλυτικά Προγράμματα Σπουδών - Κουκουνάρας- Λιάγκης, Μ.; Κολάση, Δ. (Εκπαιδευτικός Κύκλος, 2020)
Religion is a key theme in the learning process that aims to design, reflect, and transform knowledge in order for students to acquire the ability to: reflect on issues of social, economic, political and cultural pluralism, take reflective action which leads to responsible citizenship, bring about transformation and social change, enable understanding, and manage diversity through synthesis, collaboration, dialogue and creative debate, while cultivating a consciousness that leverages any local and differring elements. The above pedagogical approaches to the curriculum are presented here, focusing on the role of knowledge of religion in preschool and first-school education. The local environment, the family, the person‟s religion, and other persons of religion in the environment at pre-school and of pre-school age, have a role to play in the process of constructing the personal identity that is carried out in school by meaningful personal experiences. This process of giving meaning requires the student to know the language, to be literate and in this case the religious language. Literacy in the early years of school is fundamental to a child's development and maturity. Religious literacy is therefore essential from an early age, since it has a profound effect. Therefore, it is about the zone of proximal development, i.e. the functions that have not yet matured but are in the process of maturing.